TURISMO GASTRONÓMICO Y SU AVANCE TURÍSTICO EN EL PUERTO SANTA ANA EN LA CIUDAD DE GUAYAQUIL 2022. - Figueroa Mina, Evelyn Adriana (2022)
The present project involves the development of gastronomic tourism and its tourism promotion in Puerto Santa Ana, the possibility of implementing a tourism project in Puerto Santa Ana. Research shows that gastronomic tourism in the last decades has experienced an enormous growth and importance far beyond what is established at the classic table as it is called. This growth is reflected in many popular gastronomic destinations around the world, growth driven by investments and construction of buildings, plazas, museums and commercial establishments such as restaurants, bars, cafes and restaurants, leading to increased tourism demand in advertising and marketing strategies in this area from partnerships with local businesses. Thanks to its promotion strategy in social networks, tourism has grown and diversified continuously for decades, making it one of the fastest growing industries in the world. Global tourism is closely related to development, one of which is the growing number of new tourist destinations. These dynamics have made tourism in the port of Santa Ana one of the main drivers of Guayaquil's socioeconomic development.